THE IMPACT OF INNOVATIVE STRATEGIES ON BUSINESS COMPETITIVENESS IN THE MODERN ECONOMY - Briukhovetska, Iryna (Current Problems of Sustainable Development, 2026)
The article examines the impact of innovative strategies on business competitiveness in the modern economy. Theoretical approaches to the interpretation of the concept of “innovation strategy” are analyzed, and its role in ensuring long-term competitive advantages of enterprises is determined. The study summarizes the scientific views of leading researchers on the relationship between innovation, strategic development, and adaptation of enterprises to dynamic market conditions. Particular attention is paid to the approaches of I. Ansoff, M. Porter, J. Schumpeter, H. Mintzberg, P. Drucker, C. Christensen, and B. Twiss regarding the strategic importance of innovation activity in business development. The article identifies the main models of innovation strategy implementation, including technological, platform-service, and process-oriented approaches. The practical aspects of innovative development are analyzed through the examples of international and Ukrainian companies such as Apple, Tesla, Amazon, Google, Samsung, Rozetka, Nova Poshta, and Monobank. It is proved that systematic implementation of innovations contributes to technological leadership, improvement of business process efficiency, strengthening of market positions, and formation of sustainable competitive advantages. The research substantiates that innovation strategies in the modern economy are not only a factor of enterprise growth but also a necessary condition for business survival in a highly competitive environment. It is emphasized that effective innovation management requires a comprehensive approach combining strategic planning, flexibility, adaptation to environmental changes, and customer orientation. The study concludes that enterprises capable of continuously generating and implementing innovations achieve dynamic competitiveness and gain opportunities for sustainable long-term development in the global economic space. In addition, the article highlights the importance of digital transformation and investment in research and development as  key drivers of innovative growth. Special attention is also paid to the role of innovation culture in increasing organizational adaptability and maintaining competitive stability in conditions of economic uncertainty.
Keywords: innovation strategy; competitiveness; innovations; business; strategic management; digitalization; competitive advantages; economic development; enterprise; modern economy